1995
DOI: 10.1159/000236932
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cord-Blood-Derived Human Mast Cells Cultured in the Presence of Steel Factor and lnterleukin-6

Abstract: We generated > 107 mast cells by culturing 107 cord blood mononuclear cells for > 10 weeks in the presence of Steel factor, interleukin-6 and prostaglandin E2. 99% of the cultured cells had tryptase-positive granules, while 18% had chymase-positive granules. Cultured mast cells contained 3.6 μg histamine and 3.5 μg tryptase per 106 cells. Cells sensitized with 1 μg/ml human IgE released 58.5% histamine and 1.55 ng tumor necrosis factor (TNF)-α per 106 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
73
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 3 publications
(3 reference statements)
2
73
0
Order By: Relevance
“…HMC-1 (a kind gift of J. H. Butterfield, Mayo Clinic, Rochester, MN) and primary cultured HMCs (PCHMCs) from cord blood were maintained as described (50,51). Briefly, HMC-1 cells were cultured in IMDM (Life Technologies, Grand Island, NY) with 10% heat-inactivated FBS (Life Technologies), 4 mM L-glutamine, and antibiotics in a humidified 5% CO 2 incubator (50).…”
Section: Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…HMC-1 (a kind gift of J. H. Butterfield, Mayo Clinic, Rochester, MN) and primary cultured HMCs (PCHMCs) from cord blood were maintained as described (50,51). Briefly, HMC-1 cells were cultured in IMDM (Life Technologies, Grand Island, NY) with 10% heat-inactivated FBS (Life Technologies), 4 mM L-glutamine, and antibiotics in a humidified 5% CO 2 incubator (50).…”
Section: Cellsmentioning
confidence: 99%
“…The cell number was adjusted to 5 ϫ 10 5 cells/ml twice weekly by adding fresh media. The PCHMCs were derived from human cord blood CD34 ϩ cells grown in the presence of stem cell factor, IL-6, and IL-10, as modified from the procedure of Saito et al (51). Briefly, heparin-treated umbilical cord blood was purchased from Advanced Biotechnologies (Columbia, Maryland).…”
Section: Cellsmentioning
confidence: 99%
“…The presence of SCF alone is sufficient to direct human hematopoietic progenitors to become MC in vitro (3)(4)(5)(6). SCF is the most potent promoter of MC survival and priming, and also induces their activation (7,8).…”
mentioning
confidence: 99%
“…5A) were generated as reported (42). Toluidine blue and tryptase staining confirmed that the purity of the mast cells exceeded 90%.…”
Section: Human Mast Cells Expressed Integrin ␣ Iib ␤ 3 and Mediated Amentioning
confidence: 99%
“…Human cord blood-derived mast cells were generated from CD34 ϩ cord blood cells, as described (42). Mast cells with 90% purity were generated by 8 wk of culture in the medium containing 10% FCS, 100 ng/ml human SCF, and 50 ng/ml human IL-6.…”
Section: Cellsmentioning
confidence: 99%